Study of fine needle aspiration cytology of lymphadenopathy in tertiary care centre of Ahmedabad, Gujarat - Dr. Renu I. Sharma; Dr. Chetankumar M. Dharaiya (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Lymph nodes are a site for organized collections of lympho-reticular tissue and are pink gray bean shaped encapsulated organs. Lymphadenopathy is one of the most common clinical presentations of patients attending the outpatient department. Lymph nodes are among the commonly aspirated organs for diagnostic purposes. Fine-needle aspiration cytology (FNAC) is a clinical technique used to obtain cells, tissues and/or fluid through a thin needle attached with disposable syringe for the purpose of diagnosis of masses. Aims and Objectives: The aims of this study is to find out the frequency of lymphadenopathy, etiological factors and cyto-morphologial features in different age groups and incidence of various lymph node diseases on fine-needle aspiration cytology (FNAC) and to analyze the utility and diagnostic importance of FNAC in lymph node diseases. Materials and Methods: The present study was carried out in Department of Pathology at GMERS Medical College, Sola-Ahmedabad, Gujarat a Tertiary Care Centre.A total of 268 patients of all age groups underwent FNAC of enlarged lymph nodes during this study period. Results: Tuberculous lymphadenitis was recorded as the most common presentation of lymphadenopathy in the cervical region. Male to female ratio is 1:1.13. Most common causes of lymphadenopathy in 11-40 years age group was tubercular lymphadenitis and metastatic carcinoma in patients >50 years of age. Conclusion: FNAC of lymph nodes is an excellent first line investigation to determine the nature of lesion. It is quick, safe, minimally invasive, and reliable and is readily accepted by the patient.